The use of soft power in China's Middle East policy : 1990-2010 - Rashid, Ammar Ahmed (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study explores the Chinese foreign policy towards the countries of the Middle East from 1990 to 2010. It examines the use of soft power that has been adopted as a strategy in the Chinese foreign policy towards the Middle East to analyse the increase of Beijing's role and influence in the region. The concept of "soft power" as opposite to "hard power" has been introduced in the field of international relations. Most countries today prefer to use soft power i.e. diplomatic and peaceful means in dealing with other nations. China is one of the countries that have chosen to adopt soft power policy as a strategy in its foreign relations with various regions of the world, including the Middle East. The objectives of this research are firstly to explore the key objectives of China's foreign policy towards the Middle East. Secondly, identify the key components of China's soft power policy in the Middle East. Thirdly, examine whether or not China's soft power policy has increased Beijing's role and influence in the region. The study adopted the "soft use of power" approach introduced by Li Mingjiang. The study revealed that the preservation of national security, economic and social prosperity and international prestige are the key goals of China's foreign policy in the Middle East. The study also found that the diplomatic and economic policies represent the key components of China's soft power policy in the Middle East. Generally, China's role and influence in the Middle East were growing constantly and continuously during 1990-2010. This is likely to continue to grow at a greater pace in the coming years.